RANCANG BANGUN SISTEM INFORMASI PEMANTAUAN KESEHATAN KARYAWAN PADA PT XYZ DEPOK - Muhammad Yasin; Teddy Setiady; Muhammad Ikhsan Gimnastiar (POLITEKNIK LP3I JAKARTA, 2024)
The importance of employee health in an industrial environment has prompted companies to focus on employee well-being to increase productivity and reduce maintenance costs. However, many companies still face challenges in managing employee health effectively. In this article, we propose solutions through the development of health monitoring systems based on information and communication technology. This system provides benefits not only for employees but also for companies in the analysis and planning of interventions to improve overall employee health and productivity.